2017
DOI: 10.1002/lary.26999
|View full text |Cite
|
Sign up to set email alerts
|

Potential treatment for vocal fold scar with pirfenidone

Abstract: NA. Laryngoscope, 128:E171-E177, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…We previously showed in a preliminary in vitro study that PFD exerted antifibrotic effects, especially in terms of reducing collagen type I expression levels and gel contraction, but it did not affect the mRNA level of α‐SMA in fibroblasts isolated from ferret VF scars . We also showed that, based on its gross and microscopic VF anatomies, surgical feasibility, and response to scar‐producing injury, the ferret seems to be an excellent model for VF studies .…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…We previously showed in a preliminary in vitro study that PFD exerted antifibrotic effects, especially in terms of reducing collagen type I expression levels and gel contraction, but it did not affect the mRNA level of α‐SMA in fibroblasts isolated from ferret VF scars . We also showed that, based on its gross and microscopic VF anatomies, surgical feasibility, and response to scar‐producing injury, the ferret seems to be an excellent model for VF studies .…”
Section: Discussionmentioning
confidence: 94%
“…Then, saline alone or PFD resuspended in saline (1.0 mg/mL) was injected into the right LP of each scarred VF. The concentration was determined following studies that have used PFD in vitro . The VFs were exposed as described above, and transoral injections (~200 μL) were performed (under an operating microscope) using a Cattelan needle (Zeitels infusion needle) attached to a microsyringe.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations